Characterization of tensile properties and viscoelasticity of PTFE woven fabrics at elevated temperature. Issue 6 (March 2019) - Wang, Ruiliu; Xu, Guangbiao; He, Yuechao
An experimental study was conducted to systematically investigate the effects of temperature on the tensile properties and viscoelasticity of PTFE woven fabrics. The ultimate strength retention after heat treatment was basically 95% or higher, even treated at 260℃ for six hours. However, significant reductions of modulus and ultimate strength during tensile tests at elevated temperature were observed. Creep behaviors of PTFE woven fabrics at elevated temperature can be fitted by Burgers model, and the parameters extracted from the model can be used to analyze the instantaneous elastic strain, time-dependent strain and permanent deformation. The rod-like structure of the PTFE molecular chain and high degree of crystallinity are proposed to explain why PTFE woven fabrics have good heat stability, whereas large deformation, or even creep failure, will happen at elevated temperature.